THE EFFECT OF CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSETS (ROA), AND RETURN ON EQUITY (ROE) ON STOCK GROWTH IN STATE-OWNED BANKS LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2013-2022 PERIOD - Wahyu , Didin Rasyiddin; Majid, Abdul; Widodo, Wahyu; Munawaroh, Munawaroh; Komarudin, Mamay (Bina Bangsa International Journal of Business and Management, 2024)
The purpose of the study is to find out whether CAR, ROA and ROE affect Stock Growth in state-owned banks listed on the Indonesia Stock Exchange (IDX) for the 2013-2022 period. This research method uses a quantitative research method, the population in this study is all state-owned banks totaling 4 banks and the sample used is 4 state-owned banks using saturated samples, data collection techniques using secondary data, data analysis techniques used in this study consist of statistical descriptions, classical assumption tests, multiple linear regression analysis, determination coefficients and statistical hypotheses. Based on the results of the study, it is known that the CAR count is -5,988 < ttable -2,028 and the t-test sig is 0.000 < 0.05, the ROA t-2,213 < ttable 2,028 and the t-test sig is 0.033 < 0.05, the ROE tcount value is 7,654 < ttable 2,028 and the t-test sig is 0.000 < 0.05, and the results of the F test (simultaneous) are obtained The calculation is 78,723 > 2.86 Ftabel and the test sig value is 0.000 < 0.05. Thus, it can be concluded that partially CAR has a negative effect on Stock Growth, ROA has a negative effect on Stock Growth, and ROE has a positive effect on Stock Growth. Meanwhile, simultaneously CAR, ROA, and ROE affect Stock Growth in SOEs listed on the Indonesia Stock Exchange for the 2013-2022 period.